Notes about the bryoflora of Sierra Central de Caurel (Lugo, Spain) - Reinoso Franco, Juan; Viera Benítez, María del Carmen (Lazaroa, 2014)
Chorological notes on some taxa little known or recoder for the first time for the bryo flora of Lugo province are apported. Specially interesting are: Frullania fragilifolia, Marsupella emarginata, Metegeria conjugata, Nardia compressa, Porella cordeana, Porella pinnata y Porella platyphylla